TEST THE POTENTIAL GROWTH AND YIELD OF PLANTS PAK CHOI (Brassica rapa Subsp. chinensis (L.) Hanelt Var. Green) THROUGH HYDROPONICS SYSTEM-NUTRIENT FILM TECHNIQUE AT THE LEVEL OF THE CONCENTRATION OF NUTRIENTS ®AB MIX - Frisky Fernando Rembet; Frangky J. Paat; Jemmy Najoan (Sam Ratulangi University, 2021)
This study aims to obtain the results of the growth and production of pak choi plants. The level of nutrient concentration of ®AB Mix in this treatment is the independent variable, while the dependent variable is the pak choi plant. This study was arranged in a Randomized Block Design with 4 treatments and 3 replications, the factors studied were the concentration of AB mix nutrients with the following treatments: (P0) (Control), (P1) 900ppm, (P2) 1100 ppm and (P3) 1300 ppm. The results showed that the best plant height was produced at the nutrient concentration level of ®AB Mix in the treatment of 1100 ppm (P2) with an average of 15.35 ppm and 1300 ppm (P3) 16.23 cm. The growth parameters on the longest plant roots were produced at the level of nutrient concentration ®AB Mix 1100 ppm (P2) with an average of 25.536 cm and 1300 ppm (P3) with an average of 26,097 (P3) cm. The best fresh weight of plants was produced at the level of nutrient concentration ®AB Mix in the treatment of 1100 ppm (P2) 196.67 gr and 1300 ppm (P3) with an average of 236.67 gr (P3). Environmental variables with an average morning temperature of 28°C, 32°C during the day, 26°C at night, 60% humidity in the morning, 30% humidity during the day and 89% humidity at night for 42 days after planting.Keywoards: Hydroponic; Agroecotechnology; Pak Choi. AbstrakPenelitian ini bertujuan untuk mendapatkan hasil pertumbuhan dan produksi tanaman pak choi. Taraf konsentrasi nutrisi ®AB Mix pada perlakuan ini sebagai variabel bebas (independent variable) sedangkan variabel terikat (dependent variable) adalah tanaman pak choi. Penelitian ini disusun dalam Rancangan Acak Kelompok dengan 4 perlakuan dan 3 ulangan, faktor yang diteliti adalah konsentrasi nutrisi AB mix dengan perlakuan : (P0) (Kontrol), (P1) 900ppm, (P2) 1100 ppm dan (P3) 1300 ppm. Hasil penelitian didapatkan bahwa tinggi tanaman terbaik dihasilkan pada taraf konsentrasi nutrisi ®AB Mix pada perlakuan 1100 ppm (P2) dengan rataan 15,35 ppm dan 1300 ppm (P3) 16,23 cm. Parameter pertumbuhan pada akar tanaman terpanjang dihasilkan pada taraf konsentrasi nutrisi ®AB Mix 1100 ppm (P2) dengan rataan 25,536 cm dan 1300 ppm (P3) dengan rataan 26,097 (P3) cm. Bobot segar tanaman terbaik dihasilkan pada taraf konsentrasi nutrisi®AB Mix pada perlakuan 1100 ppm (P2) 196,67 gr dan 1300 ppm (P3) dengan rataan 236,67 gr (P3). Variabel lingkungan dengan rataan suhu pagi hari 28°C, Siang hari 32°C, malam hari 26°C, rataan kelembaban 60% pada pagi hari, kelembaban 30% pada siang hari dan kelembaban 89% pada malam hari selama 42 hari setelah tanam.Kata kunci: Hidroponik; Agroekoteknologi; Pak Choi.